Sistema de informações de custos: uma proposta para a Universidade Tecnológica Federal do Paraná - Stolf, Tatiane Hlatchuk (2018)
Anchored in the principles of efficiency, effectiveness and economy, the public administration must seek to meet the needs of citizens, acting in order to obtain the best possible use in the use of public resources. Thus, public administration has the constant challenge of improving the quality of spending by optimizing resources to reach the satisfaction of users of public services. In this context, the Federal Government's Cost Information System presents itself as a tool capable of assisting the public manager, both in decision-making, and in monitoring and evaluating the performance of government achievements. In view of the need for cost information to assist in the control and decision making process of the managers, the general objective of the work was to propose a cost measurement model for the Federal University of Technology - Paraná, using the SIC - Cost Information System of the Federal Government. The methodology used was the action research, by the insertion of the researcher in the research environment, and involved the diagnosis of the institution regarding the tools and information available, seeking to cover the entire structure and categories of university spending. For the delineation of the proposed model, the most costly objects of UTFPR were first identified, then the cost centers and their coding were defined. Following, the institution's expense categories were analyzed, identifying those that will be considered costs, and establishing the procedures for generating cost information, as well as the reports to be issued through the SIC at the end of the period to be analyzed. The objects and cost centers were established based on the institution's final macroprocesses and the courses offered, to allow a comparison of their costs. It was found that the most representative category of expenditure is that related to Personnel and Charges and that special attention should be given to this category. It was highlighted the need for investment in training and awareness of the servers involved with the generation of cost information, combined with a simple and gradual introduction of the system, in order to minimize possible resistances and to allow the process continuity and the improvement of the tool.